Gambaran Faktor Intrapersonal dan Kepatuhan Minum Obat Pada Pasien Hipertensi - Umi Hanik; Dafid Arifiyanto (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Hypertension is a chronic disease with a high prevalence that requires long-term medication adherence and is infkuenced by various intrapersonal factors. This study aimed to describe intrapersonal factors and medication adherence among patients with hypertension. This study employed a quantitative design with a cross-sectional approach. The research was conducted in the working area of Kesesi II Community Health Center. The sampling technique used was total sampling involving 162 respondents. Instrument used to assess intrapersonal factors included the Perceives Stress Scale, Rosenberg Self-Esteem Scale, Hamilton Depression Rating Scale, self-discipline questionnaire, and Alcohol Use Disorders Identification Test. Medication adherence was measured using the Morisky Medication Adherence Scale. The validity test of self-discipline questionnaire showed a calculated r- value ranging from 0.401 to 0.557 (> r table). Data were analyzed using univariate analysis. The average age of respondents was 59 years, and the majority were female, with 124 respondents (76.5%). Most respondents experienced moderate stress, with 142 respondents (87.6%), and were not depressed, with 160 respondents (98.7%). The majority had high self-esteem, with 134 respondents (82.7%), high self-discipline, with 158 respondents (97.5%), and no risk og alcohol misuse, with 162 respondents (100%). Most respondents demonstrated high medication adherence, with 126 respondents (77.8%). Gypertensive patients generally showed good intrapersonal factors, which were in line with high medication adherence. The findings of this study are excpted to be considered in providing nursing care for patients with hypertension through the assessment of intrapersonal factors, health education, and monitoring of medication adherence to support optimal hypertension management.